Parental Awareness About School Backpack, Weight Carried by Their Children and related Musculoskeletal Problems - Dhakal Chalise, Gita; Sherpa, Samjhana; Bharati, Mamata; KC, Ambu (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Backpacks are a convenient means to carry essential educational materials for school children. Backpack design, carrying technique and its load is related to several health consequences i.e., altered gait, bad posture and musculoskeletal pain. Parental awareness and their supervision can help their children to carry appropriate school backpack with rationale weight. Therefore, this study aims to assess parental awareness about school backpacks; identify backpack weight carried by their children and identify children’s musculoskeletal complaints with their parents. Methods: A descriptive cross-sectional study design was used. The study consisted of purposively selected 94 parents whose children were studying in grade VI to VIII at local school. Face to face interview of around 30 minutes duration was taken by using semi structured interview schedule. Backpack weight was identified by weighing children with and without bag in their school and subtracted to identify the actual backpack weight. Data was analysed by using SPSS version 20 and described by using descriptive statistics. Results: In this study, more than 90% parents were aware of the recommended weight of school backpack i.e., <15% of body weight. About 96% parents answered that backpack should be light; similar percentage told that it should have well-padded shoulder straps and 87% answered that it should be appropriate to child’s age and weight. Around 70% to 90% parents were aware of appropriate handling of school backpacks. While identifying parental awareness about musculoskeletal effects of backpacks, they told as shoulder pain (79%), fatigue (76%) and neck pain (56%). In this study, 72% children were carrying backpacks greater than the recommended weights. Their parents told that children often had complaints of shoulder pain (78%) and neck pain (69%) Conclusions: Most parents were aware of the standards and handling of school backpack but in reality, more than two third of their children were carrying heavy school backpacks.